PENGARUH PROFITABILITAS, LEVERAGE, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP INCOME SMOOTHING: STUDI EMPIRIS PADA PERUSAHAAN PENERBANGAN TERBAIK ASIA - Purnomo, Nadia (Media Akuntansi dan Perpajakan Indonesia, 2020)
Airlines company particularly Asia’s airlines has dealing hard timesespecially when global crisis in 2008, that impacts towards aviation. Companieswould do anything to maintain their existence. One of them is toperform income smoothing practices. An evidence found that one of the topairlines companies according to SKYTRAX has been performing incomesmoothing practices in the year of 2018, that was PT Garuda Indonesia.This indicating that others top airlines companies as well potentially performingincome smoothing to maintain companies wholeness and evenachieving to be top Asia’s airlines companies. This research aims to determinefactors that influence the income smoothing practice in Asia’s topairlines companies. The variable used in this research are profitability, leverage,and institutional ownership. This research used quantitative approachwith the use of multiple linear regression analysis technique. This researchused 2008-2018 annual report period observed from eleven Asia’s airlinescompanies. The sampling method used in this research is purposive samplingwith 121 data. The results show that profitability, leverage, and institutionalownership have a negative effect on income smoothing.